Interaction between IGF2‐PI3K axis and cancer‐associated‐fibroblasts promotes anal squamous carcinogenesis. Issue 7 (18th February 2019) - Cacheux, Wulfran; Lièvre, Astrid; Richon, Sophie; Vacher, Sophie; El Alam, Elsy; Briaux, Adrien; El Botty, Rania; Mariani, Pascale; Buecher, Bruno; Schnitzler, Anne; Barbazan, Jorge; Roman‐Roman, Sergio; et al.
Abstract : Anal squamous cell carcinoma (ASCC) is a rare tumour, but its incidence is increasing. Standard chemoradiotherapy fails to cure 20% of patients and no targeted therapy is currently approved for recurrent ASCC. The PI3K/Akt/mTOR pathway is frequently altered in this poorly characterised carcinoma. IGF2 was identified here as a key factor in ASCC oncogenesis, as IGF2 was shown to play a crucial role in the PI3K pathway with frequent ( 60%) and mutually exclusive genomic alterations in IGF2, IGF1R, PTEN and PIK3CA genes. We also demonstrated that IGF2 expression is mainly due to cancer‐associated fibroblasts and that IGF2 secreted by cancer‐associated fibroblasts from ASCC samples promotes proliferation of a human ASCC cell line via IGF2 paracrine signalling. Altogether, these results highlight the key role of the IGF2/PI3K axis, and the major role of cancer‐associated fibroblasts in tumour growth via IGF2 secretion, suggesting a major role of IGF2/IGF1R inhibitors in ASCC therapies. Abstract : What's new? Anal squamous cell carcinoma (ASCC) is a rare tumour, but its incidence is rising. The etiological role of human papillomavirus (HPV) infection and the importance of the PI3K/Akt/mTOR pathway are now well established. Nonetheless, ASCC remains a poorly characterised carcinoma. Here, the authors show a key role of IGF2 and cancer‐associated fibroblasts (CAFs) in ASCC, pointing to the potential use of IGF2/IGF1R inhibitors to improve treatment of this cancer. Thus, abnormalities in the IGF2/PI3K pathway displayed by ASCC are both frequent and mutually exclusive; and IGF2 secreted by CAFs promotes direct tumour growth.